Fabrication of conductive oxidase-entrapping nanocomposite of mesoporous ceria–carbon for efficient electrochemical biosensor1. Issue 96 (17th October 2015) - Kang, Eunae; Lee, Jinwoo; Won, Byoung Yeon; Kim, Seongbeen; Shin, Sujeong; Kim, Moon Il; Park, Hyun Gyu
<x xml:space="preserve">Abstract</x> A conductive oxidase-entrapping nanocomposite in mesostructured ceria (CeO2)–carbon is developed for electrochemical detection of H2O2 and glucose without any mediators.